Baroreflex activation therapy for the treatment of heart failure with reduced ejection fraction in patients with and without coronary artery disease. (1st September 2018) - Halbach, Marcel; Abraham, William T.; Butter, Christian; Ducharme, Anique; Klug, Didier; Little, William C.; Reuter, Hannes; Schafer, Jill E.; Senni, Michele; Swarup, Vijay; Wachter, Rolf; Weaver, Fred A.; et al.
Abstract: Background: In a randomized trial, baroreflex activation therapy (BAT) improved exercise capacity, quality of life and NT-proBNP in patients with heart failure with reduced ejection fraction (HFrEF). In view of different mechanisms underlying HFrEF, we performed a post-hoc subgroup analysis of efficacy and safety of BAT in patients with and without coronary artery disease (CAD). Methods and results: Patients with left ventricular ejection fraction <35% and NYHA Class III were randomized 1:1 to guideline-directed medical and device therapy alone or plus BAT. Patients with a history of CAD, prior myocardial infarction or coronary artery bypass graft were assigned to the CAD group with all others assigned to the no-CAD group. Of 71 BAT treated patients, 52 had CAD and 19 had no CAD. In the control group, 49 of 69 patients had CAD and 20 had no CAD. The system- or procedure-related major adverse neurological or cardiovascular event rate was 3.8% in the CAD group vs. 0% in the no-CAD group (p = 1.0). In the whole cohort, NYHA Class, Minnesota Living with Heart Failure score, 6-minute hall walk distance and NTproBNP were improved in BAT treated patients compared with controls. Statistical analyses revealed no interaction between the presence of CAD and effect of BAT (all p > 0.05). Conclusion: No major differences were found in BAT efficacy or safety between patients with and without CAD, indicating that BAT improves exercise capacity, quality of life and NTproBNP in patients with ischemic and non-ischemic cardiomyopathy. ClinicalTrials.gov identifier: NCT01471860 andNCT01720160 . Highlights: Etiology-dependent effects of BAT in HFrEF were analyzed. Exercise capacity, quality of life and NTproBNP improved under BAT. Efficacy and safety were equal in patients with and without coronary artery disease. BAT is effective and safe in ischemic and non-ischemic cardiomyopathy.